Connectivity between sea turtles off Jeju Island on the Korean Peninsula, and other populations in the western Pacific - Jang, Sook-Jin; Jo, Kyungsik; Jang, Soojin; Nishizawa, Hideaki; Kim, Miyeon; Balazs, George; Im, Jibin; Suk, Ho Young; Kim, Byung-Yeob; Kim, Taewon (Frontiers in Marine Science, 2024)
The northwestern Pacific region is an important habitat for sea turtles, hosting five species out of seven. There is still limited information available about the sea turtle aggregations around the Korean Peninsula, which is the northern boundary for many sea turtle species in the western Pacific area. The present study aims to investigate the migratory route of sea turtles visiting Jeju Island. Five species of sea turtles were identified from by-catch and stranding data between 2013 and 2022 on Jeju Island in Korea: green (Chelonia mydas; 24 individuals), loggerhead (Caretta caretta; 9), hawksbill (Eretmochelys imbricata; 2), olive ridley (Lepidochelys olivacea; 2), and leatherback (Dermochelys coriacea; 1). Mixed stock analysis using mitochondrial DNA haplotypes revealed that Jeju green turtles primarily originate from the rookeries of the Japanese Archipelago. This connectivity between two regions was also supported by the similar genetic composition of loggerhead turtles. Similarly, satellite tracking data showed that several green turtles originating from Jeju Island migrated to waters near the Ryukyu Archipelago in Japan. Nevertheless, about 60% of the tracked green turtles stayed near Jeju Island, with most overwintering there, indicating the long residency in Jeju Island. This study also provides the genetic sequences of other three species including new orphan haplotypes of hawksbill and olive ridley turtles. Our findings suggest that Jeju Island serves as a stable foraging habitat and provide insight into understanding the habitat range of sea turtles in the western Pacific.